Isolation and Genomic Identification of Salmonella Pullorum in the Poultry Farms of Nepal - Khanal, D.R.; Pokhrel, R.; Bajracharya, N.; Khanal, S.; Shrestha, P. (Nepalese Veterinary Journal, 2017)
In the present study, Salmonella pullorum bacteria were isolated from 30 liver samples of poultry collected during the postmortem examination of suspected cases of pullorum disease from five major poultry producing districts (Kathmandu, Lalitpur, Bhaktapur, Kavre and Chitwan) of central Nepal in 2014. After isolating bacterial colonies from 30 samples in Brilliant Green Agar (BGA) and Xylose Lysine Deoxycholate (XLD) agar media, biochemical tests carried out for the identification of bacteria. On carbohydrate fermentation tests, 25 isolates showed metabolic characteristics typical for Salmonella while genomic analysis performed with Polymerase Chain Reaction (PCR) by amplifying Salmonella pullorum specific rfbs gene (187 bp) targeting Adenine residue at 237 positions confirmed that 18 isolates were from poultry suffering from pullorum disease. Present result warranted the need for routine biochemical and genomic investigations for better understanding of the species of Salmonella prevalent and subsequent adoption of suitable control strategy in the poultry operation.